TESTING AND EVALUATION OF BIOACTIVE COMPOUNDS IN SOYBEAN - Albandary Nasser Alsaloom (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to estimate the antioxidants, antibacterial, and antifungal activities of methanolic extract from soybean seeds against pathogenic microorganisms. The methanolic extract was prepared from defatted soybean flour. Total phenolics content (TPC), total flavonoid content (TFC), and the major phenolic, flavonoid, and isoflavone compounds in soybean extract were estimated by HPLC. On the other hand, biological activities such as antioxidants, antibacterial, and antifungal activities were evaluated. The value of phenolic compounds was 8.59 mg GAE/g extract, while the value of flavonoids was 0.82 mg QE/g extract. The chemicals listed below were chromatographed and identified: syringic acid, quercetin, gallic acid, benzoic acid, genistein, daidzein, p-coumaric acid, glycitein, and ferulic acid. The methanolic extract showed the antibacterial and antifungal activity against tested microorganisms. Considering the results, it is possible to employ the methanolic extract from soybean seeds, which is rich in phenolic chemicals, as an antioxidant, antibacterial, and antifungal agent. It functions well as a pure, natural product.